Online Project-based Learning Integrated Quizizz as a Formative Assessment to Trigger High Order Thinking Skills - Mahendra, I Wayan Eka (Universitas Pendidikan Ganesha, 2022)
The Covid-19 pandemic has caused various impacts in the learning process, one of which is learning loss. Learning loss will directly and indirectly affect higher order thinking skills. This study aims to analyze the difference in HOTS between students who take Online Project-based Learning integrated quizizz as a formative assessment and HOTS students who take regular online learning. This study involved a population of 129 people and a sample of 39 people who were determined by random sampling technique. This type of research is a quasi-experimental research, with a non-equivalent control group design. The instrument used to collect data is the HOTS test in the form of a description. The data obtained were analyzed using one-way ANOVA, which had previously been tested for prerequisites. All data analysis using the help of IBM's SPSS for Windows 16.0. The results of data analysis show that there are differences in HOTS between students who take Online Project-based Learning integrated quizizz as a formative assessment and HOTS of students who take regular online learning. For this reason, teachers are expected to apply Quizizz's integrated Online Project-based Learning as a formative assessment in learning to obtain maximum higher-order thinking skills.